International monetary economics - Machlup, Fritz, 1902-1983 (Routledge library editions. Economics, 2003)
Containing Fritz Machlup's papers on international finance spanning thirty years, this volume includes pieces translated into English for the first time. Focussing on the theme of the balance of payments, the work is structured as follows: Foreign Exchanges and Balance of Payments, The Effects of Devaluation, Gold and Foreign Reserves, Capital Movements and the Transfer Problem. An introduction to each section by the author is included.